2018
DOI: 10.1016/j.bar.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

East meets West: When the Islamic and Gregorian calendars coincide

Abstract: Recent research has documented that at the time of religious celebrations in Muslim countries, such as Ramadan, there is a "festival" effect in share returns. In the Gregorian calendar, December is also a time of celebration and festivities which may be associated with patterns in the behaviour of security prices. Further, the first month of the year in the Islamic calendar, Muharram, is a time of sadness and mourning for some believers, and there may be an effect when the Islamic first month of the year overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…Thus in the case of an Islamic country such as Pakistan it appears that there may be a Ramadan effect and a January effect; the interaction between these two periods, when they occur at the same time, has been largely ignored in the literature. A multi-country investigation by Abadir and Spierdijk (2005) More relevant to our study, Tantisantiwong et al (2017) investigated Eastern (Islamic) and Western (Gregorian) calendar effects, including the effect of when Ramadan and January coincide and found that the results are more prominent in larger and more developed markets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in the case of an Islamic country such as Pakistan it appears that there may be a Ramadan effect and a January effect; the interaction between these two periods, when they occur at the same time, has been largely ignored in the literature. A multi-country investigation by Abadir and Spierdijk (2005) More relevant to our study, Tantisantiwong et al (2017) investigated Eastern (Islamic) and Western (Gregorian) calendar effects, including the effect of when Ramadan and January coincide and found that the results are more prominent in larger and more developed markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, these two anomalies have usually been studied in isolation; only Tantisantiwong et al (2017) has recognised that the Ramadan and January effects overlap from time to time. The current paper addresses these issues by first investigating whether the Ramadan effect exists in the mean and volatility of equity returns for 428 firms across four countries with predominantly Muslim populations: namely, Indonesia, Jordan, Pakistan and Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Ramadan effect had a non-persistent impact. Tantisantiwong et al (2018) investigate interactions among different calendar effects, in particular, between Ramadan and January effects in equity returns and volatilities. The results suggest that share returns and volatility on the days of Ramadan tend to be higher when these days falls in January.…”
Section: Ramadan Effect In the Cryptocurrency Marketsmentioning
confidence: 99%
“…Moreover, the Ramadan effect had a non-persistent impact. Tantisantiwong et al. (2018) investigate interactions among different calendar effects, in particular, between Ramadan and January effects in equity returns and volatilities.…”
Section: Literature Review: Seasonal Anomaliesmentioning
confidence: 99%
“…They found an amplified impact of Ramadan on stock returns when it overlaps with January. Tantisantiwong et al (2018) studied the overlapping impact of Islamic and Gregorian calendars on seven Muslim countries during the period 1995 and 2016. They documented that the overlapping effect of Islamic and Gregorian calendars was amplified in larger companies and in more developed markets.…”
Section: Literature Reviewmentioning
confidence: 99%